Fuzzy systems and data mining II proceedings of FSDM 2016 - Sun, Shilei (Frontiers in artificial intelligence and applications ;, 2016)
Fuzzy systems and data mining are now an essential part of information technology and data management, with applications affecting every imaginable aspect of our daily lives.